2014
DOI: 10.1142/s0217979214501288
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Li+ doping on the quenching concentration of 2H11/2/4S3/2 level of Er3+

Abstract: Li + and Er 3+ codoped Y 2 O 3 powders are synthesized via sol-gel method. The effects of Li + doping on the optical properties of Er 3+ :Y 2 O 3 are investigated under 980 nm excitation. The emission intensity of Er 3+ is obviously improved after Li + doping. Moreover, the quenching concentration of 2 H 11/2 / 4 S 3/2 level of Er 3+ is 3.0 mol% for the samples without Li + but it decreases to 2.0 mol% after introducing 5.0 mol% Li + . This is because Li + doping shrinks the host lattice and decreases the Er 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…To assess the effect of Li addition on the local structure of Ln–Y 2 O 3 , we select Eu (1%), Sm(0.1%), Tb(1%), and Dy (1%) as the luminescence probes. ,, Selection of Li concentration at 5% is close to the value reported as optimal, above which a decline in the emission intensity of Ln activators is typically observed. ,, ,,,,, Depending on the synthesis procedure, the type of lanthanide (co)­dopants, and the way the emission was induced (down- or up-conversion excitation), smaller (2, 3%) ,,,,, or greater (10%) optimal Li concentrations were also determined. To this point, we note that in most studies, the actual Li concentration is not confirmed by quantitative analysis (i.e., inductively coupled plasma mass spectrometry), ,, and thus the value may be lower than the nominal one.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To assess the effect of Li addition on the local structure of Ln–Y 2 O 3 , we select Eu (1%), Sm(0.1%), Tb(1%), and Dy (1%) as the luminescence probes. ,, Selection of Li concentration at 5% is close to the value reported as optimal, above which a decline in the emission intensity of Ln activators is typically observed. ,, ,,,,, Depending on the synthesis procedure, the type of lanthanide (co)­dopants, and the way the emission was induced (down- or up-conversion excitation), smaller (2, 3%) ,,,,, or greater (10%) optimal Li concentrations were also determined. To this point, we note that in most studies, the actual Li concentration is not confirmed by quantitative analysis (i.e., inductively coupled plasma mass spectrometry), ,, and thus the value may be lower than the nominal one.…”
Section: Resultsmentioning
confidence: 99%
“…The absorption and emission transition probabilities of Ln are governed by site-specific selection rules: for C 2 sites, both magnetic (MD) and electric dipole (ED) transitions are allowed, while for S 6 sites only the magnetic dipole transitions are allowed, leading generally to emissions with order(s) of magnitude less intense than those of C 2 sites . According to the literature, upon Li codoping of Ln–Y 2 O 3 , the small ionic radius of Li (0.76 Å compared to 0.9 Å for Y, in 6-fold coordination) enables facile insertion into Y 2 O 3 lattice, either substitutionally ,,,,, or both substitutionally and interstitially ,,,,,,, generating strain and charge imbalance. Several scenarios have been advanced to explain the emission enhancement by Li addition: (i) the oxygen vacancies resulted from the charge-compensation can remove the inversion symmetry of S 6 site, and thus the forbidden electric dipole transitions become allowed, leading to an increased number of optically active lattice sites; ,, , (ii) Li preferentially substitutes for C 2 site, further reducing the local symmetry; (iii) Li addition can reduce the local symmetry at both sites; , ,,, and (iv) the Ln–Ln interactions get weaker via breaking the Ln–Ln clusters in addition to reduced local symmetry. ,,, …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations